ANALISIS FRAMING PEMBERITAAN KELANGKAAN MINYAK GORENG PADA MEDIA INEWS.ID - Laili, Laili Suryani; Haryo Kusumo Aji (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2025)
The analysis of cooking oil scarcity is an important study in understanding market dynamics and its impact on society. In recent years, this scarcity phenomenon has triggered various economic and social problems. This study aimed to identify the factors that cause the scarcity of cooking oil, including price fluctuations and government policies. The target of this study was news about